Between power and plenty : foreign economic policies of advanced industrial states - Katzenstein, Peter J. (Madison : University of Wisconsin Press, 1978)
The relation of domestic structure to foreign economic policy is the integrating theme of this valuable set of papers by younger scholars. Originally it was an issue of International Organization.
Originally published as the autumn 1977 issue of International organization, vol. 31, no. 4.
Includes bibliographical references and index.
rpm 05/04/2018
Loans
Keywords: International economic relations; Commercial policy; Economic policy